A comparison of the pharmacological profiles of prasugrel and ticagrelor assessed by platelet aggregation, thrombus formation and haemostasis in rats. (12th April 2013) - Sugidachi, A; Ohno, K; Ogawa, T; Jakubowski, JA; Hashimoto, M; Tomizawa, A
<x xml:space="preserve">Abstract</x> Background and Purpose Prasugrel is a third‐generation thienopyridine prodrug and ticagrelor is a non‐competitive P2Y12 receptor antagonist. In their phase 3 studies, both agents reduced rates of ischemic events relative to treatment with clopidogrel. Experimental Approach The pharmacodynamic profile of anti‐platelet effects of prasugrel was compared with that of ticagrelor in rats. Key Results The active metabolite of prasugrel was less potent than ticagrelor and its active metabolite on platelet aggregation in vitro. In contrast, prasugrel was a more potent antiplatelet agent than ticagrelor on ex vivo platelet aggregation: their ED50 values at peak for ADP 20 μmol·L−1 were 1.9 and 8.0 mg·kg−1, respectively. Prasugrel's inhibition of platelet aggregation was maintained for up to 24 h after administration, but ticagrelor's duration of action was substantially shorter. Prasugrel and ticagrelor significantly inhibited thrombus formation with ED50 values of 1.8 and 7.7 mg·kg−1, respectively. Both agents also prolonged bleeding times (ED200 values of 3.0 and 13 mg·kg−1 respectively) suggesting that at equivalent levels of inhibition of platelet aggregation, the agents would show comparable antithrombotic activity with similar bleeding risk. Platelet transfusion significantly increased blood platelet numbers similarly in prasugrel‐ and ticagrelor‐treated rats. In the prasugrel‐treated group, platelet transfusion caused significant shortening of bleeding time, while in the ticagrelor‐treated group, platelet transfusion showed no influence on bleeding time under the experimental conditions employed. Conclusions and Implications Prasugrel and ticagrelor showed several differences in their pharmacological profiles and these disparities may reflect their differing reversibility and/or pharmacokinetic profiles.